2020
DOI: 10.3390/nu12092640
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of the Changes in the Food Choice Determinants of Secondary School Students: Polish Adolescents’ COVID-19 Experience (PLACE-19) Study

Abstract: During the outbreak of Coronavirus Disease 2019 (COVID-19) pandemic and the lockdown, various changes of dietary habits are observed, including both positive and negative ones. However, the food choice determinants in this period were not studied so far for children and adolescents. The study aimed to analyze the changes in the food choice determinants of secondary school students in a national sample of Polish adolescents within the Polish Adolescents’ COVID-19 Experience (PLACE-19) Study population. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 43 publications
(58 reference statements)
6
85
0
7
Order By: Relevance
“…The PLACE-19 Study was designed as a population-based study to be conducted in a national sample of Polish secondary school students recruited from all regions and voivodeships of Poland. The PLACE-19 Study included a first phase (April 2020) that assessed hand hygiene [ 25 ] and personal protective behaviors [ 26 ] during the COVID-19 pandemic and a second phase (May 2020) that assessed food choice determinants [ 27 ] and appetitive traits during the COVID-19 pandemic. Secondary schools included in the first phase were excluded from the stratified sampling procedure in the second phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLACE-19 Study was designed as a population-based study to be conducted in a national sample of Polish secondary school students recruited from all regions and voivodeships of Poland. The PLACE-19 Study included a first phase (April 2020) that assessed hand hygiene [ 25 ] and personal protective behaviors [ 26 ] during the COVID-19 pandemic and a second phase (May 2020) that assessed food choice determinants [ 27 ] and appetitive traits during the COVID-19 pandemic. Secondary schools included in the first phase were excluded from the stratified sampling procedure in the second phase.…”
Section: Methodsmentioning
confidence: 99%
“…The PLACE-19 Study was conducted in a group of secondary school students aged 15–20 years, who were chosen using a random quota sampling procedure, as described previously [ 27 ]. From the national secondary schools database, a representative sample of schools was chosen while using a stratified sampling procedure.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, an online survey conducted in Poland in May 2020 among 2448 adolescents aged 15–20 years suggested that the pandemic may have brought positive changes promoting the uptake of a better diet [ 11 ]. It revealed that health and weight control were the main determinants of food choices of adolescents during the COVID-19 pandemic compared to before the pandemic, outstripping the sensory appeal of food and mood ( p < 0.0001).…”
Section: The Ripple Effects Of the Covid-19 Pandemic On Nutrition Andmentioning
confidence: 99%
“…As of recently, more studies have been published on COVID-19 lockdown effects on dietary habits, as well as on other lifestyle behaviors [ 5 , 6 , 7 , 17 , 18 ]. However, most of the previous studies focused on adult population, and only few studies have been published so far about COVID-19 lockdown influence on lifestyle change in adolescents [ 19 , 20 , 21 ] and in medical students [ 22 , 23 ]. Hence, we aimed to investigate dietary habits and other related lifestyle behaviors changes in adolescents and medical students resulting to COVID-19 lockdown in Croatia.…”
Section: Introductionmentioning
confidence: 99%